Crumpled and Eccentric Nanospheres of Ti3C2Tx MXene by Aerosol Jet Printing on Heat Substrate. Issue 8 (24th February 2022) - Wu, Yu; Lin, Aiping; Zhang, Jidi; Zhao, Danjiao; Bai, Xiaojing; Lu, Cheng; Wang, Shufen; Fan, Lanlan; Cao, Lei; Liu, Sida; Gu, Feng
Abstract : 2D MXene has attracted tremendous attention for developing high‐performance energy storage devices regarding its good metallicity and relatively large accessible surface area. However, the electrochemical performance of MXene‐related devices was hindered due to the pronounced self‐stacking characteristic of MXene. Herein, a convenient aerosol jet printing (AJP) process is developed for the synthesis of MXene nanospheres with crumpled and eccentric structures by modulating the migration and assembly of MXene nanosheets on heat substrate. The existing temperature gradient between the apex and the edge of the deposited droplet causes thermocapillary flows carrying MXene nanosheets toward the edge and the MXene nanosheets are further shaped and assembled along the droplet surface during the solvent evaporation. Interdigital microelectrodes of crumpled MXene nanospheres are tentatively developed for electrochemical performance characterization, a competitive areal capacitance performance is demonstrated in comparison with other MXene‐based devices. Importantly, this work highlights the great potential of the AJP technique for developing functional devices with fascinating hierarchical features as well as further extending applications in miniaturized and intelligent microelectronics. Abstract : A convenient aerosol jet printing (AJP) process has been developed for the synthesis of MXene nanospheres with crumpled and eccentric structures by exploiting microscale aerosol droplets as microreactors. The existing temperature gradient of the sessile droplets dominates the migration and assembly of MXene nanosheets with increased interlayer distance upon deposition temperature.